Conservation agriculture in Africa climate smart agricultural development - Mkomwa, Saidi; Kassam, A. H. (CAB International, 2022)
"Conservation Agriculture (the use of no tillage systems) to preserve soil structure and integrity has become an increasingly important step towards sustainable farming. This book brings together conservation agriculture and climate smart decision making processes for the first time, focusing on Africa"--